Humor in Times of COVID-19 in Spain: Viewing Coronavirus Through Memes Disseminated via WhatsApp - Cancelas-Ouviña, Lucía-Pilar (Frontiers in Psychology, 2021)
The COVID-19 crisis has generated a big social stress on a global scale due to the situation of confinement we have experienced. In Spain, we have been isolated in our homes without being able to interact physically with family members, friends or co-workers. Each of us has used different resources to face up this stressful, new and unexpected situation (fitness, reading, painting, meditation, mindfulness, dancing, listening to music, playing instruments, cooking, etc). One of the resources and strategies that we have used most often is to use humour as a means of putting into perspective the seriousness of the situation or to make the day-to-day more bearable. Humour is something very cultural that varies from one country to another and is part of the idiosyncrasy of each culture and is a particular characteristic feature of the Spanish personality. During the COVID-19 crisis, the main means or channel of communication was the social networks and throughout the confinement there was an excessive flow of humorous memes concerning the Coronavirus and everything we experienced during the National State of Emergency decreed by the Spanish Government. The memes denote great irony, ingenuity and especially many creativity doses to make an experience that has been very hard and stressful more bearable. In this paper we will use a qualitative methodology based on ethnography research carrying out ethnographic fieldwork on the memes disseminated through WhatsApp during the long-term period of confinement lived in Spain (14th March-21st June 2020). We will frame the memes in the Netlore, a digital contemporary folklore, presenting a theoretical framework on memes and humour and its different functions in order to channel of grief, fear and suffering or to play specific situations down. We will proceed to categorize and analyse a corpus of 644 memes that have flooded social networks, showing how the Spanish have managed to bring out their humorous and creative vein in difficult times to criticize political decisions, to show their frustrations, to describe their new normal, to interact with others, to anticipate the future, etc.